Polissemia em phrasal verbs: uma concepção semântico-cognitiva de análise e aplicação didática - Vieira, Sarah Lúcia Alem Barbieri Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Tem esta tese o objetivo de descrever e analisar o processo de formação dos phrasal verbs da língua inglesa e posterior extensão semântica que dá origem às diferentes acepções convencionalizadas e registradas em dicionários especializados do idioma. A definição de phrasal verb, nesta pesquisa, limita-se a uma locução verbal constituída por um verbo lexical e uma partícula adverbial (two-word verb), cujo significado total da construção não pode ser depreendido pela simples somatória dos significados individuais dos termos integrantes. São construções tradicionalmente rotuladas de idiossincrasias lexicais pelo fato de impetrarem enorme dificuldade de classificação, denominação, interpretação, uso, além de representar grande empecilho no âmbito do ensino-aprendizagem do inglês como língua estrangeira (ILE) ou segunda língua (ISL). Partindo da concepção de que a forma emana do sentido e que os itens lexicais (ILs) são categorias conceptuais que representam uma rede de significados e sentidos distintos, mas relacionados, que exibe efeitos prototípicos, a pesquisa desenvolvida enquadra-se no domínio da Semântica Lexical Cognitiva, abordando a dimensão semasiológica-qualitativa. A fundamentação teórica-metodológica é embasada pela Teoria da Integração e Desintegração Conceptual e os construtos cognitivos empregados como ferramentas na operalização são: os “frames semânticos”, os “esquemas de imagem”, os “espaços mentais” e os “domínios conceptuais”. O corpus analisado foi selecionado a partir de dois critérios: (i) familiaridade conceptual (phrasal verb knock out) e (ii) frequência de uso (phrasal verb go on). A seleção das acepções obedeceu somente ao critério frequência de uso no British National Corpus (BNC) e dicionários especializados da língua inglesa. Os contextos...

The purpose of this thesis is to describe and analyze the process of how phrasal verbs are formed in English, and further semantic extension as a source of different meanings conventionalized and found in specialized dictionaries in English. In this research the definition of phrasal verb is limited - two-word verbs consisting of a lexical verb and an adverbial particle, which the meaning cannot be deduced by simply adding the meanings of the terms. These constructions are traditionally labeled lexical idiosyncrasies because they are seen as enormously difficult to classify, describe, interpret, use, and represent major hindrance in the teaching and learning of English as a Foreign Language (EFL) or Second Language (ESL). Based on the assumption that form derives from meaning, and that lexical units are conceptual categories representing a network of meanings and distinct meanings, yet related, exhibiting prototypical effects, the research developed fits in the field of Cognitive Lexical Semantics, semasiological-qualitative dimension approach. The theoretical-methodological approach is based on the Conceptual Disintegration and Conceptual Integration Theory and the cognitive constructs employed as tools for operating are: semantic frames, image schemas, mental spaces and conceptual domains. The corpus analyzed was selected based on two criteria: (i) conceptual familiarity (phrasal verb knock out) and (ii) frequency of use (phrasal verb go on). The selection of the senses obeyed only the criterion of frequency used in the British National Corpus (BNC) and specialized dictionaries in English. The contexts analyzed were taken from the web corpus, two criteria were determined: (i) authenticity of the material and (ii) accessibility, according to the level of understanding considered B2 (high intermediate), corresponding to the standards... (Complete abstract click electronic access below)
Keywords: Língua inglesa; Língua inglesa - Estudo e ensino; Polissemia; Semantica; Polysemy